Page_5otherConjuring Ghosts of the Past: Landscapes and Hauntings in Jane Urquhart's The Stone Carvers. Issue 1 (14th November 2018) - Handley, Agata
Abstract : Jane Urquhart's novel The Stone Carvers (2001) portrays the struggles of a community of German immigrants in the nineteenth century, as they attempt to settle in Western Ontario; it also includes a fictionalized account of the construction of the Canadian National Vimy Memorial 1 (for First World War Canadian dead, and missing, presumed dead, in France). The article explores the issues of dealing with loss, and re-living the past, which are interwoven by Urquhart into a larger narrative, forming an ongoing meditation on the experience of 'in-betweenness'— transgressing not only spatial, but also temporal boundaries— and incorporating individual and communal histories as they are passed on through generations. The lives of Urquhart's characters are marked by the ambivalence of belonging— the experience of having more than one homeland, in more than one landscape. They are haunted by lost places, and by the memory of people who perished as a result of war, or who they left behind in the course of their own personal journey. The article explores the issue of 'landscape biography', and also examines Urquhart's employment of the literary topoi of nekuia/katabasis (i.e., encounters with the dead). It demonstrates how the confrontation with the past becomes, in the novel, a prerequisite for regeneration of the present, and the establishment of the future.